Phenotypic divergence of traits that mediate antagonistic and mutualistic interactions between island and continental populations of the tropical plant, Tribulus cistoides (Zygophyllaceae) - Winer Daniel Reyes‐Corral; Sofia Carvajal‐Endara; Molly Hetherington‐Rauth; Jaime A. Chaves; Peter R. Grant; B. Rosemary Grant; Andrew P. Hendry; Marc T. J. Johnson (Ecology and Evolution, 2023)
Abstract Island systems have long served as a model for evolutionary processes due to their unique species interactions. Many studies of the evolution of species interactions on islands have focused on endemic taxa. Fewer studies have focused on how antagonistic and mutualistic interactions shape the phenotypic divergence of widespread nonendemic species living on islands. We used the widespread plant Tribulus cistoides (Zygophyllaceae) to study phenotypic divergence in traits that mediate antagonistic interactions with vertebrate granivores (birds) and mutualistic interactions with pollinators, including how this is explained by bioclimatic variables. We used both herbarium specimens and field‐collected samples to compare phenotypic divergence between continental and island populations. Fruits from island populations were larger than on continents, but the presence of lower spines on mericarps was less frequent on islands. The presence of spines was largely explained by environmental variation among islands. Petal length was on average 9% smaller on island than continental populations, an effect that was especially accentuated on the Galápagos Islands. Our results show that Tribulus cistoides exhibits phenotypic divergence between island and continental habitats for antagonistic traits (seed defense) and mutualistic traits (floral traits). Furthermore, the evolution of phenotypic traits that mediate antagonistic and mutualistic interactions partially depended on the abiotic characteristics of specific islands. This study shows the potential of using a combination of herbarium and field samples for comparative studies on a globally distributed species to study phenotypic divergence on island habitats.